Superior mesenteric vein and portal vein thrombosis in a patient with COVID-19: a rare case. Issue 6 (22nd June 2021) - Jeilani, Milad; Hill, Robert; Riad, Mahmud; Abdulaal, Yasser
Abstract : A 68-year-old man was referred to the general surgeons on account of his abdominal pain of unknown cause. He had contracted COVID-19, 9 days prior. CT chest abdomen and pelvis revealed an extensive thrombus extending from the portal vein to the superior mesenteric vein. Further investigation ruled out haematological causes, and COVID-19 was determined to be the cause. He was treated with an extended course of therapeutic dose low molecular weight heparin under the guidance of the haematology team. He was discharged once he was clinically stable and pain-free, with a plan to be followed up by both the surgeons and haematologists. This case highlights the different ways in which COVID-19 presents, and the need for clearer guidance on the treatment and prevention of thromboembolism in COVID-19.